MicroRNA-95-3p inhibits cell proliferation and metastasis in colorectal carcinoma by HDGF - Yong-gang Hong; Zhi-ping Huang; Qi-zhi Liu; Ji-Fu E; Xian-hua Gao; Cheng Xin; Wei Zhang; Pengpeng Li; Li-qiang Hao (Biomedical Journal, 2020)
Background: MicroRNAs (miRNAs) play an important regulatory role in carcinogenesis and cancer progression. MiR-95-3p has been reported to be an oncogene in hepatocellular carcinoma. However, the role of miR-95-3p in colorectal carcinoma (CRC) remains unclear. Methods: miR-95-3p was validated in an independent validation sample cohort of 215 CRC tissues. Functional assays, Cell proliferation (MTT) assay colony formation, wound healing, transwell and animal xenograft assays were used to determine the oppressor role of miR-95-3p in human CRC progression. Furthermore, Bioinformatics analysis, western blotting and dual-luciferase reporter assay were used to determine the mechanism by which miR-95-3p suppresses progression of CRC cells. Results: In this study, we found that miR-95-3p was downregulated in CRC tissues. The low level of miR-95-3p in CRC tumors was correlated with aggressive clinicopathological characteristics, and it predicted poor prognosis in CRC patients. The overexpression of miR-95-3p significantly inhibited CRC cell proliferation, colony formation and metastasis in vitro and in vivo. Bioinformatic analysis further identified hepatoma-derived growth factor (HDGF) as a novel target of miR-95-3p in CRC cells. These findings suggest that miR-95-3p regulates CRC cell survival, partially through the downregulation of HDGF. Conclusions: Therefore, the miR-95-3p/HDGF axis might serve as a novel therapeutic target in patients with CRC.